CURCUMIN AND ITS EFFECT ON PREECLAMPSIA: AS ANTI-INFLAMMATORY, ANALGESIC, AND ANTICOAGULANT - FADINIE, WULAN; LELO, AZNAN; WIJAYA, DADIK WAHYU; LUMBANRAJA, SARMA NURSANI (International Journal of Current Pharmaceutical Research, 2020)
Objective: Based on the Indonesia Health Profile In 2014, almost 30% of maternal deaths at Indonesia in 2010 were caused by hypertension in pregnancy, which one of them was preeclampsia. Many theories said to be the risk factor, such as acute body inflammation. Its clinical symptoms are hypertension, upper abdominal pain, and haemorrhage. Nowadays, many studies have been developed to predict the onset of preeclampsia, one of which is COX-2. This study was the first one to examine the benefits of curcumin in preeclamptic patients around the world. This study aims to discover whether curcumin affects the level of COX-2, VAS, and anticoagulant factors in preeclamptic patients. Methods: This is true experimental research with a double-blind randomized design. 50 samples were collected within a period of 7 mo and were divided into 2 groups: Case and Control Group. A total of 3 blood tests were conducted: prior, 90 min, and 12 h after case/treatment. Results: 4 samples were eliminated during preparation. The total number of samples was 46; 23 in Control Group and 23 in Case Group. In this study, we found clinical changes in the level of COX-2, VAS and anticoagulant factors in patients given 100 mg of curcumin compared to those who were not. In addition, we also found a correlation between clotting time and bleeding time at T2 where both time factors became shorter. Conclusion: There was a statistically significant decrease in COX-2 level in the Case Group, which led to decreased value of VAS, shorter clotting time and lower thrombocyte count; and, there was a significant correlation found between clotting time and bleeding time at T2 in the preeclamptic patients.